The messenger : Moderna, the Vaccine, and the Business Gamble That Changed the World - Loftus, Peter, (Peter D.) (Boston, Massachusetts : Harvard Business Review Press, 2022)
"At the start of 2020, Moderna was a waning biotech unicorn, still years away from delivering its first product despite a decade of development of a potentially breakthrough innovation: using RNA to combat disease. Investors were getting antsy or, worse, skeptical. Then the coronavirus pandemic hit, and Moderna became a central player in a global drama-a David to pharma's Goliaths-turning its technology toward breaking the global grip of the terrible disease. By year's end, as the outbreak was at its worst, Moderna delivered one of the world's first Covid-19 vaccines, with a stunningly high rate of protection. The achievement not only offered the world a way out of a crippling pandemic but also validated Moderna's gene-based technology, transforming the company into a global industry power, swelling its market value on its prospects for new drugs and vaccines for years to come. Biotech, and the venture capital community that fuels it, will never be the same. Wall Street Journal reporter Peter Loftus, part of a Pulitzer Prize-finalist reporting team and 25-year veteran reporter in the pharmaceutical and biotech industries, brings the inside story of how Moderna went all in on a single revolutionary idea; of quiet research with unknown consequence; of the evolution of a cutting-edge American innovation, industry, and economy-decades in the making-that led to one of the great gambles in business history"
Prologue. Disease X -- Changing the Fate -- If This Is True -- Kendall Square -- Feeding the Beast -- Broke Offer -- No Boundaries -- mRNA- -- More Money -- Warp Speed -- Hold On, Help Is On the Way -- Politics Protocols and Patents -- The Power of Science -- Evidence -- Happy Tears -- Delta -- Just the Beginning.
Includes index
Keywords: Moderna (Firm) -- History; Vaccines industry -- History; Pharmaceutical biotechnology industry -- Economic aspects -- History; Messenger RNA